Successful Use of Epidural Blood Patch for Postdural Puncture Headache Following Lumbar Sympathetic Block. Issue 4 (July 1996) - Lehmann, Lance J.; Hacobian, Asteghik; DeSio, John M.
Abstract : Background and Objectives: A 21-year-old man was scheduled for a diagnostic lumbar sympathetic block for reflex sympathetic dystrophy of the right lower extremity. Methods: The patient experienced paresthesias with possible puncture of a dural sleeve during needle placement under fluoroscopy. After discharge, the patient developed a positional headache, which increased in intensity over 48 hours. An epidural blood patch was subsequently performed. Results: The patient obtained complete relief from the headache. Conclusion: Postdural puncture headache resulting from leakage of cerebrospinal fluid through a punctured dural sleeve may be successfully treated with an epidural blood patch should more conservative treatments fail.